Estudio de la cinética de adsorción y desorción de colorantes aniónico y catiónico usando una arcilla con altos contenidos de hierro. - Guaypatin Pico, Jefferson Raúl (2020)
Adsorption and desorption experiments were performed for a cationic and an anionic dye, using clay with high iron contents as an adsorbent to study the kinetics of these phenomena. Adsorption was studied by varying the contact time between adsorbate and adsorbent for different clay doses, and the effect of pH, solute concentration, and adsorbent dose were analyzed. In contrast, the study of desorption was carried out by applying the thermochemical regeneration method, using Ethanol, HCl, and combinations of solvents. The Freundlich and Temkin isotherms had better results for the cationic dye case, and the Temkin and DubininRadushkevich isotherms were better for the anionic one. For both dyes of diverse ionic nature, the kinetic model that R2 best presented was the pseudo-second-order, but it was also determined that a higher concentration of solute in solution, the mayor will be the intraparticle diffusion that will be experienced. On the other hand, the desorption revealed that the anionic dye could be removed in greater quantity than the cationic due to the adsorbent's affinity.